Chinese political involvement and new trends in reaction : a post-2008 general election analysis - Lee, Yok Fee (2008)
The 2008 Malaysian general election result has surprised many parties and also indirectly altered the traditional assumptions on the nature of the relationship among the multiracial people in the country. There are three main parts in this paper. First part is to provide a background on the Malaysian government’s management of pluralism, especially in maintaining the stable ethnic relations since the country’s independence in 1957. In the second part, the author further looks into some ethnic related issues faced by the Chinese and the methods used to engage the issue prior to the 2008 general election. In the last part, the author analyzes some new trends occurred in Malaysian Chinese’s reactions or perceptions towards the role of Chinese dominant political parties (namely Malaysian Chinese Association, Malaysian People’s Movement Party and Democratic Action Party) in the mist of the Malay hegemony.